Veronica Mars and philosophy : investigating the mysteries of life (which is a bitch until you die) - Dunn, George A., 1957- (Hoboken : John Wiley & Sons Inc., 2014)
"A collection of essays centered on philosophical issues brought forth in Veronica Mars, the critically acclaimed neo-noir detective series set in the fictional town of Neptune, California."--Provide by publisher.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Veronica Mars (Television program); Veronica Mars (Television program); PERFORMING ARTS -- Reference; Electronic books